The environmental effect on galaxy evolution: Cl J1449 + 0856 at z = 1.99. Issue Volume 15:Issue S359(2020) (March 2019) - Coogan, Rosemary T.; Daddi, E.; Gobat, R.; Sargent, M. T.
Abstract: This work focuses on understanding the formation of the first massive, passive galaxies in clusters, as a first step to the development of environmental trends seen at low redshift. Cl J1449 + 0856 is an excellent case to study this - a galaxy cluster at redshift z = 1.99 that already shows evidence of a virialised atmosphere. Here we highlight two recent results: the discovery of merger-driven star formation and highly-excited molecular gas in galaxies at the core of Cl J1449, along with the lowest-mass Sunyaev-Zel'dovich detection to date.